(untitled) (Baghdad Science Journal, 2022)
Cytokines are signaling molecules between inflammatory cells that play a significant role in the pathogenesis of a disease. Among these cytokines are interleukins (ILs) 17A and 33, and accordingly, the current case-control study sought to investigate the role of each of the two cytokines in the risk of developing multiple sclerosis (MS). Sixty-eight relapsing-remitting MS (RRMS) Iraqi patients and twenty healthy individuals (control group) were enrolled. Enzyme linked immunosorbent assay (ELISA) kits were used to determine serum levels of IL-17A and IL-33. Results revealed that IL-17A and IL-33 levels were significantly higher in MS patients than in controls (14.1 ± 4.5 vs. 7.5 ± 3.8 pg/mL; p < 0.001 and 65.3 ± 16.3 vs. 49.3 ± 20.0 pg/mL; p < 0.001, respectively). Receiver operating characteristic (ROC) curve analysis demonstrated that IL-17A was a very good predictor of MS (area under curve [AUC] = 0.869; 95% CI = 0.779 - 0.960; p < 0.001; cut-off value = 10.2 pg/mL; sensitivity = 80.8%; specificity = 75.0%). A similar prediction was presented by IL-33, but the AUC value was lower (AUC = 0.762; 95% CI = 0.63 - 0.89; p < 0.001; cut-off value = 56.4 pg/mL; sensitivity = 70.6%; specificity = 70.0%). Multinomial logistic regression analysis confirmed the significance of IL-17A and IL-33 in MS risk, and under three models of analysis, the estimated odds ratios for IL-17A (1.50, 1.49 and 1.50, respectively) and IL-33 (1.05, 1.05 and 1.06) were above 1.0. Patients stratified by gender (male and female), expanded disability status scale (EDSS: < 3 and ≥ 3) or medication (pre- and post-medication) showed no significant differences in serum levels of IL-17A and IL-33 for each stratum. However, with regard to response to medication, it was found that responding patients showed significantly higher levels of IL-33 than non-responders (70.9 ± 12.2 vs. 57.2 ± 18.2 pg/mL; p = 0.018). This difference was not observed when considering IL-17A. Pearson correlation analysis between IL-17A and IL-33 revealed that both cytokines were not significantly correlated. In conclusion, the study indicated that IL-17A and IL-33 were up-regulated in serum of MS patients, and this up-regulation was not influenced by age, gender, EDSS or medication status, but the elevated level of IL-33 was more pronounced in patients who responded to medication.